Exploration of Ethnomathematics in Banyumas Traditional Food in Sokaraja Area, Central Java - Annisa Fitri Wulandari; Arif Rahman Hakim; Soeparlan Kasyadi (Edumatica: Jurnal Pendidikan Matematika)
This study aims to explore the ethnomathematics concepts found in traditional Banyumas foods and their potential as mathematics teaching materials for junior high school students. Using an ethnographic approach within a qualitative research framework, data were collected through observation, interviews, field notes, and documentation. The study results indicate that traditional Banyumas foods, such as rempeyek, nopia, and getuk goreng, contain various mathematical concepts. These concepts are reflected in the shapes of the food, cooking utensils, and packaging, resembling two-dimensional shapes like squares and circles, as well as three-dimensional shapes like cylinders, cubes, and half-spheres. Additionally, the concept of similarity is also observed in certain aspects of the food and its utensils. Based on these findings, the researchers recommend integrating ethnomathematics concepts of measurement and shape from traditional Banyumas foods into mathematics learning media. This approach is expected to make the learning process more enjoyable and meaningful, as it combines mathematical knowledge with elements of local culture. Thus, students not only gain an understanding of mathematical concepts but also acquire insights into local cultural heritage, creating a more engaging and relevant learning experience.